Ultrafast hot electron–hole plasma photoluminescence in two-dimensional semiconductors. Issue 15 (3rd April 2023) - Sousa, Frederico B.; Perea-Causin, Raül; Hartmann, Sean; Lafetá, Lucas; Rosa, Bárbara; Brem, Samuel; Palekar, Chirag; Reitzenstein, Stephan; Hartschuh, Achim; Malic, Ermin; Malard, Leandro M.
Abstract : Pulsed laser excitation at high pump fluences inducing an exciton Mott transition to an electron–hole plasma in the as-exfoliated TMD samples at room temperature. Abstract : The transition metal dichalcogenide family of semiconducting two-dimensional materials has recently shown a prominent potential to be an ideal platform to study the exciton Mott transition into electron–hole plasma and liquid phases due to their strong Coulomb interactions. Here, we show that pulsed laser excitation at high pump fluences can induce this exciton Mott transition to an electron–hole plasma in mono and few-layer transition metal dichalcogenides at room temperature. The formation of an electron–hole plasma leads to a broadband light emission spanning from the near infrared to the visible region. In agreement with our theoretical calculations, the photoluminescence emission at high energies displays an exponential decay that directly reflects the electronic temperature – a characteristic fingerprint of unbound electron–hole pair recombination. Furthermore, two-pulse excitation correlation measurements were performed to study the dynamics of electronic cooling, which shows two decay time components, one of less than 100 fs and a slower component of few ps associated with the electron–phonon and phonon–lattice bath thermalizations, respectively. Our work may shed light on further studies of the exciton Mott transition into other two-dimensional materials and their heterostructures and its applications in nanolasers and other optoelectronic devices.